Current research in Semitic studies: proceedings of the Semitic Studies section at the 34th DOT at Freie Universität Berlin - Olivieri, Simona; Talay, Shabo (Harrassowitz Verlag, 2024)
This volume contains 22 selected papers in English and German, first presented at the 34th Deutscher Orientalistentag (DOT, www.dot2022.de) of the Deutsche Morgenländische Gesellschaft at Freie Universität Berlin from September 12 to 17, 2022 in the Semitic Studies Section. The DOT has been organized since 1921; the 34th edition in September 2022 celebrated its 100th anniversary. Due to its international scope, the DOT is one of the most important academic conferences worldwide. In 2022, about 1200 presentations, spread across 23 sections, offered insights into various disciplines and areas of regional and cultural studies. The Semitic Studies Section of the DOT featured over sixty contributions, the abstracts of which can be accessed via the DOT website. The contributions in this volume provide an overview of current research in the field of Semitic studies and present the diverse approaches and the broad spectrum of topics discussed at the conference. The 22 papers are divided into three thematic chapters. Chapter A contains contributions on general and comparative Semitics and presents research on several Semitic languages aside from Arabic. Chapter B comprises papers covering Arabic linguistics and dialectology, and chapter C consists of four contributions from a conference panel on the topic of recitation practices of sacred texts.